Cloning and Characterization of cDNA Encoding a Serine Protease Inhibitor from Salivary Glands of Thai Cattle Tick (Boophilus microplus) - Paitoon Kaewhom; Theerapol Sirinarumitr; Sirirak Chantakru; Sathaporn Jittapalapong (Agriculture and Natural Resources, 2007)
Tick salivary gland (TSG) proteins have been an evidence for application as novel tick control agents. The serine protease inhibitors (serpins) secreted from TSG may be used in an anti-tick feeding. In this study, we cloned serpin cDNA from TSG of Boophilus microplus by Reverse Transcription Polymerase Chain Reaction (RT-PCR) and analyzed its nucleotide and deduced amino acid sequences. Our results showed that the 1,200 bp open reading frame of serpins could encode a protein with 399 amino acid residues. By comparison with other serpin available in the GenBank database, the aminoacid sequence, in the reactive center loop (RCL) of the cloned serpin, demonstrated a 95% and 100% identity to those of the B. microplus and Rhiphicephalus appendiculatus, respectively. This is the first report on a cloning of cDNA encoding a serpin derived from B. microplus in Thailand. Based on this result, Thai serpin genes were homologous to the other serpins gene and confirmed a potential use of recombinant Thai serpin as the candidate antigen for vaccine to immunize cattle against B. microplus infestations.